Penafsiran Hukum Syekh Abdul Halim Hasan Tentang Kepemimpinan Laki-Laki Dalam Surat An-Nisa:34 (Studi Kitab Tafsir Ahkam) - Tuah, Mad (Institut Syekh Abdul Halim Hasan Binjai, 2024)
This study aims to analyze the legal interpretation of Sheikh Abdul Halim Hasan regarding male leadership in Surah An-Nisa: 34, as discussed in his work Tafsir Ahkam. Surah An-Nisa: 34 is a verse frequently referenced in discussions concerning gender relations, particularly in the context of household leadership and male authority. Through the Tafsir Ahkam approach, Sheikh Abdul Halim Hasan offers an understanding of the foundations of male leadership and the responsibilities it entails in accordance with Islamic law. This research employs a qualitative method with a descriptive-analytical approach, where Tafsir Ahkam serves as the primary source for examining this verse. The findings indicate that Sheikh Abdul Halim Hasan interprets male leadership in the family as an obligation based on financial capacity, spiritual guidance, and moral responsibility. However, this leadership is accompanied by justice and the protection of women's rights, ensuring that it is neither absolute nor discriminatory. This interpretation is significant for understanding the social and legal context of Islamic law and contributes meaningfully to the discourse on gender equality in Islamic exegesis.